Unilateral laterothoracic exanthema in an adult. Issue 12 (15th October 2020) - Chamli, Amal; Souissi, Asmahene; Midassi, Olfa; Mokni, Mourad
Abstract: Unilateral laterothoracic exanthema (ULE) is a benign self‐limited condition that spontaneously resolves in a few weeks. Occurring mostly in childhood, although few rare cases in adults have been also reported. Diagnosis of ULE is clinical, and laboratory investigations are not required. Abstract : Unilateral laterothoracic exanthema (ULE) is a benign self‐limited condition that spontaneously resolves in a few weeks. Occurring mostly in childhood, although few rare cases in adults have been also reported. Diagnosis of ULE is clinical, and laboratory investigations are not required.